Evaluación de dos alimentos comerciales para la reversión sexual en larvas de Oreochromis Niloticus Y Oreochromis Spp (2022)
The Aquaculture sector in the last 10 years has increased significantly, going from produce 82,622 tons of meat products including tilapia, trout, cachama, shrimp and others native species to produce 179,351 tons, representing an increase of 216%, according to data of the Ministry of agriculture for 2020. The per capita consumption of the country was 8.8 kilograms of fish per person per year and 17,569 tons of meat were destined for export. Tilapia, Trout and Shrimp for a value of 92.4 million dollars. (Minagriculture, 2020).